Economic Factor and Reading Habit: A Survey of Students’ Reading Habit in East Lombok, West Nusa Tenggara, Indonesia - Hidayatul Hamdiah; Nik Mohd Rahimi Nik Yusoff (CV. Creative Tugu Pena, 2021)
Indonesia has a School literacy Movement Program but the government rarely to survey to know the condition of students’ reading habit in eastern of Indonesia especially East Lombok, West Nusa Tenggara, Indonesia. Therefore, this research is a survey study aims to investigate students reading habit based on their description as readers and to investigate the factor (parents’ income) influence students’ reading habits of East Lombok, West Nusa Tenggara, Indonesia. This is survey design. Survey research design is quantitative research to investigate the entire population of individuals to report the population's characteristics, behaviors, attitudes, and opinions. Convenience sampling was used and the sample was 160 students. Frequency and Pearson Chi-square test used to analyze the data and it found that east Lombok students are